Priority Actions for Sustainable Forest Management in the International Year of Forests - Dellasala, D.A.; Fitzgerald, J.M.; Jonsson, B.-G.; Mcneely, J.A.; Dovie, B.D.; Dieterich, M.; Majluf, P.; Nemtzov, S.C.; Nevin, O.T.; Parsons, E.C.M.; Watson, J.E.M. (Conservation Biology, 2012)
The United Nations General Assembly (2007) proclaimed 2011 the International Year of Forests to “raise awareness at all levels to strengthen the sustainable management, conservation and sustainable development of all types of forests for the benefit of current and future generations.” Despite ongoing efforts to control the loss of forests globally (e.g., UN Programme on Reducing Emissions from Deforestation and Forest Degradation [REDD +], Conference of the Parties to the UN Framework Convention on Climate Change [UNFCCC]), this call by the UN signals that forest sustainability challenges remain substantial. The Society for Conservation Biology (SCB) is positioned to influence progress toward sustainability aspirations of the UN and others through discussions, such as the one presented in this paper, and through a related declaration on forests submitted by the regional sections of SCB (2011) to UN delegates. Our objectives here are to review broad trends in forest status, suggest improvements to forest monitoring, and suggest priority actions for advancing the sustainable management, conservation, and sustainable development of forests.
Keywords: Sustainable Forest Management; Forest; Reducing Emissions from Deforestation and Forest Degradation; Society for Conservation Biology (SCB)